Анализ магнитного поля асинхронного двигателя в различных режимах работы с использованием метода конечных элементов - Милых, Владимир Иванович; Сидоренко, Е. А.; Шилкова, Лариса Васильевна (НТУ "ХПИ", 2007)
The task of preparation of electromagnetic parameters decides for the calculation of the magnetic field in the different modes of operations of asynchronous engine with a short-circuited rotor. The result of his calculation is given actually on the basis of taking field approach and program FEMM, which is located on the site of <http://femm.berlios.de/>
Keywords: электрические машины; магнитное поле; полевые методы; электромагнитное поле; метод конечных элементов